Do Market-oriented Engendered Agriculture-health Interventions Affect Household Nutrition Outcomes: Evidence from an Orange-fleshed Sweetpotato Project in Rwanda - Bocher, T.F.; Okello, J.J.; Sindi, K.; Nshimiyimana, J.C.; Muzhingi, T.; Low, Jan W. (Informa UK Limited, 2021)
The number of agricultural interventions promoting biofortified crops as a strategy to combat micronutrient malnutrition have increased significantly during the past decade. These interventions aim to improve the intake of key nutrients and sometimes other nutrition outcomes. In this study, we assess the impact of a market-oriented gender-sensitive agriculture-health project on household food consumption and food security. We use gender-disaggregated data from 842 sweetpotato farmers and a series of econometric techniques to assess the project’s impact on food consumption household food security. The study finds unambiguous and strong impact of the project on both household food consumption and food security. Moreover, female-headed participant households benefitted much more from participation than did male-headed households. We further find that nonparticipant households would also have benefitted had they participated. The findings imply the importance of designing market-focused projects with a gender lens. They also imply that market-oriented agriculture-sensitive interventions do not necessarily harm the nutritional status of farm households.